Security Testing on Web Based Application - Punitha, A; Bai, D. Sukanya; Lavanya, K (International Journal of Computer Sciences and Engineering, 2018)
Prime objective of security testing [1] is to find out how vulnerable a system may be and to determine whether its data and resources are protected from potential intruders. Online transactions have increased rapidly of late making security testing as one of the most critical areas of testing for such web applications. Now a days, privacy and security play an important role. Software applications need to focus on data and its operations security which requires urgent attention, but it’s ignored. Security resembles the essential feature in software. In fact, our main intention is to focus on the web based testing which is one of the types of application testing with its importance, implementation and its methodologies that has been defined from developer’s point of view which is extremely helpful to the developers. Software Testing is an important process in SDLC [2] which provides assurance for quality to both software developer’s (Company) and users as well. Just like testing the performance of an application, it is also important to perform security testing before the app is open to real users. Security testing is performed to detect vulnerabilities in an application, while ensuring that the data is protected and that the application works as required .Web testing is a software testing practice to test the websites or web applications for potential bugs. It’s a complete testing of web-based applications [3] before making live. A web-based system needs to be checked completely from end-to-end before it goes live for end users [4]. By performing web site testing, an organization can make sure that the web-based system is functioning properly and can be accepted by real-time users. The UI design and functionality are the captains of website testing.